Integration of policies in framing water management problem in the Indian Himalayas: Analysing policy processes using a Bayesian network - Saravanan V. Subramanian (University of Bonn, Center for Development Research (ZEF), 2009)
While there is growing realization that IWRM policy packages are exploited by various actors, there is inadequate understanding of the integration of these in shaping and reshaping water management. This paper contributes to this understanding by analyzing this policy process using Bayesian network tool from a case study in the Indian Himalayas. The analysis reveals that multifaceted governance arrangement influencing water management. The paper reveals that in such regime, policies are never implemented, but integrated through the negotiation of diverse other policies and socio-cultural settings in shaping water resource management. In such an regime, the paper calls for policies to lay-out broad principles for multiple actors to debate and negotiate diverse other policy packages for an informed decision.
urn:nbn:de:101:1-20090923101
Keywords: 330; Policy processes; policy modeling; integrated management; Bayesian network; South Asia